Płeć a tolerancja ryzyka w inwestycjach giełdowych - Kicia, Mariusz (Gender and Risk Tolerance in Stock Market Investments, 2008)
Discoveries of behavioural finance show that decisions investors make while investing at the stock market depend on their personality and gender. Many analyses show that male investors more often females accept higher risk. The article also presents that the effect is still significant regardless of investment horizon and investment aim priority.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 272-277